2013
DOI: 10.1530/eje-12-0903
|View full text |Cite
|
Sign up to set email alerts
|

The association between papillary thyroid carcinoma and histologically proven Hashimoto's thyroiditis: a meta-analysis

Abstract: Objective: No consensus exists on the association between papillary thyroid carcinoma (PTC) and Hashimoto's thyroiditis (HT). To resolve this controversy, this study aimed to evaluate the relationship between the two conditions using a meta-analysis. Methods: We searched relevant published studies using citation databases including PubMed, Embase, and ISI Web of Science. The effect sizes of clinicopathologic parameters were calculated by odds ratio (OR), weighted mean difference, or hazard ratio (HR). The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
270
5
28

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(330 citation statements)
references
References 41 publications
27
270
5
28
Order By: Relevance
“…Although it is not statistically significant, our study showed that, the TNM staging of PTC patients in HT group had a higher proportion of stage I than the PTC patients in non-HT group. These results were compatible with the literatüre and these results can be suggestive that the tumor's biological behavior is better in the case of HT or its due to the close follow-up of HT patients for thyroid disorders (3,6,9,14).…”
Section: Discussionsupporting
confidence: 90%
“…Although it is not statistically significant, our study showed that, the TNM staging of PTC patients in HT group had a higher proportion of stage I than the PTC patients in non-HT group. These results were compatible with the literatüre and these results can be suggestive that the tumor's biological behavior is better in the case of HT or its due to the close follow-up of HT patients for thyroid disorders (3,6,9,14).…”
Section: Discussionsupporting
confidence: 90%
“…This wide distribution of coexisting CLT and PTC may at least in part be due to differences in histological examination and criteria of autoimmunity characterization, patient selection or indications for thyroidectomy, population background and, mainly, environmental factors (2). A recent meta-analysis demonstrated that the occurrence rate of CLT was 2.8 times higher in patients with PTC compared to patients with benign thyroid diseases (7) and 2.4 times higher in patients with PTC than in those with other histopathological types (7). Albeit indirectly, these results suggest that patients with CLT might well present a stronger predisposition toward the development of PTC.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with high thyroglobulin levels may have had pathological conditions causing thyroglobulin elevation, such as chronic thyroiditis, as the background of resected thyroid glands. Lee et al (30) reported that papillary carcinoma was significantly associated with pathologically confirmed chronic thyroiditis. However, further studies are required in order to investigate this possibility.…”
Section: Calcification (+) Calcification (-) ------------------------mentioning
confidence: 99%